Hubungan Tingkat Kepatuhan Konsumsi PMT Lokal dengan Status Gizi Balita Wasting di Puskesmas Bulakamba Brebes - Ida Eliyah; Setyaningsih, Sulasyi; Wahyani, Anggray Duvita (Universitas Muhadi Setiabudi, 2025)
Wasting is a form of malnutrition reflected in a child's weight being too low for their height. Wasting is caused by several factors, including direct and indirect causes. First, direct causes are dietary intake or infection, or a combination of both. One effective approach to addressing malnutrition in toddlers is to provide nutrient-rich supplementary foods. Compliance with the consumption of local supplementary foods is considered a determining factor in the success of nutritional interventions. The purpose of this study was to analyze the relationship between compliance with local supplementary foods (PMT) and the nutritional status of wasted toddlers. This study was conducted in the Bulakamba Community Health Center (Puskesmas) area of Brebes Regency. This was a quantitative observational study with a cross-sectional design. Most (63.7%) of wasted toddlers who were given local supplementary foods were compliant with their supplementary foods, while 36.3% were non-compliant. Most (60%) of wasted toddlers experienced an improvement in their nutritional status to normal, while 40% of wasted toddlers did not experience any improvement in their nutritional status. The results of the chi-square test on the variable level of compliance with nutritional status obtained a p value <0.05 (p = 0.037). There is a significant relationship between the level of compliance with local supplementary food consumption and the nutritional status of wasting toddlers.